2014 International Conference on Lightning Protection (ICLP) 2014
DOI: 10.1109/iclp.2014.6973344
|View full text |Cite
|
Sign up to set email alerts
|

Lightning return stroke current reconstruction or vertical and variable channel shape

Abstract: First a new mathematical approach is presented to evaluate the electric and magnetic field of the lightning, via engineering model with variable shape return stroke channel; next, an inverse procedure is exposed for the reconstruction of both spatial and temporal waveforms of the lightning return stroke current, throughout a numerical field synthesis procedure, based on regularization of ill-posed problems. The approach uses as input data the acquisition of time domain recordings of electric and/or magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Ceclan et al. (2011, 2013, 2014) achieved the lightning current reconstruction by applying electromagnetic fields in various locations and at various frequencies. Also, Andreotti et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceclan et al. (2011, 2013, 2014) achieved the lightning current reconstruction by applying electromagnetic fields in various locations and at various frequencies. Also, Andreotti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Delfino et al (2003) measured vertical electric field at different positions and reconstructed lightning current by integral equation between field and current. Ceclan et al (2011Ceclan et al ( , 2013Ceclan et al ( , 2014 achieved the lightning current reconstruction by applying electromagnetic fields in various locations and at various frequencies. Also, Andreotti et al (2001) identified the return stroke current in frequency domain.…”
Section: Introductionmentioning
confidence: 99%